How to improve the efficiency of our brain? - Grzegorz Zurek,; Sarna, Michal; Zurek, Alina; Gorski, Ewa; Dalaunay, Gerda (Technium Social Sciences Journal, 2020)
The efficiency of the brain greatly contributes to a person’s intelligence quotient (IQ), which may ultimately affect one’s social status. Neurophysiological processes and IQ change during a person’s lifetime and depend on a number of factors, including fluid and crystalized intelligence, diet, physical activity and sleep. As described in the literature, the level of fluid intelligence decreases with age. This process can be delayed by implementing mental exercises and physical factors in one’s lifestyle. The SOMECO concept developed in Germany and described in this paper emphasizes the importance of following the most current scientific research in maintaining overall mental health.